Clinical Significance of PTEN Deletion, Mutation, and Loss of PTEN Expression in De Novo Diffuse Large B-Cell Lymphoma - Xiaoxiao Wang; Xin Cao; Ruifang Sun; Charlene Tang; Alexandar Tzankov; Jun Zhang; Ganiraju C. Manyam; Min Xiao; Yi Miao; Kausar Jabbar; Xiaohong Tan; Yuyang Pang; et al. (Neoplasia: An International Journal for Oncology Research, 2018)
PTEN loss has been associated with poorer prognosis in many solid tumors. However, such investigation in lymphomas is limited. In this study, PTEN cytoplasmic and nuclear expression, PTEN gene deletion, and PTEN mutations were evaluated in two independent cohorts of diffuse large B-cell lymphoma (DLBCL). Cytoplasmic PTEN expression was found in approximately 67% of total 747 DLBCL cases, more frequently in the activated B-cell–like subtype. Nuclear PTEN expression was less frequent and at lower levels, which significantly correlated with higher PTEN mRNA expression. Remarkably, loss of PTEN protein expression was associated with poorer survival only in DLBCL with AKT hyperactivation. In contrast, high PTEN expression was associated with Myc expression and poorer survival in cases without abnormal AKT activation. Genetic and epigenetic mechanisms for loss of PTEN expression were investigated. PTEN deletions (mostly heterozygous) were detected in 11.3% of DLBCL, and showed opposite prognostic effects in patients with AKT hyperactivation and in MYC rearranged DLBCL patients. PTEN mutations, detected in 10.6% of patients, were associated with upregulation of genes involved in central nervous system function, metabolism, and AKT/mTOR signaling regulation. Loss of PTEN cytoplasmic expression was also associated with TP53 mutations, higher PTEN-targeting microRNA expression, and lower PD-L1 expression. Remarkably, low PTEN mRNA expression was associated with down-regulation of a group of genes involved in immune responses and B-cell development/differentiation, and poorer survival in DLBCL independent of AKT activation. Collectively, multi-levels of PTEN abnormalities and dysregulation may play important roles in PTEN expression and loss, and that loss of PTEN tumor-suppressor function contributes to the poor survival of DLBCL patients with AKT hyperactivation.